CRYSTAL CHEMISTRY OF BASIC LEAD CARBONATES. I. CRYSTAL STRUCTURE OF SYNTHETIC SHANNONITE, PB2O(CO3) - Krivovichev S.V.; Burns P.C. (My University, 2000)
The crystal structure of synthetic shannonite, Pb2O(CO3), orthorhombic, P2(1)2(1)2(1), a = 5.1465(7), b = 9.014(1), c = 9.315(1) Angstrom, V = 432.12(10) Angstrom (3), Z = 4, has been solved by direct methods and refined to R = 0.054. There are two symmetrically distinct Pb2+ cations in irregular coordination polyhedra due to the effect of stereoactive s(2) lone-electron pairs. The structure can be described as composed of chains of [OPb2] composition running parallel to [100] that are built by corner-sharing of OPb3 oxocentred triangles. The [OPb2] chains are surrounded by CO3 groups to form complex [OPb2](CO3) chains that are linked into a 3-dimensional framework by additional Pb-O bonds. The structure has channels that are parallel to [100] in which the lone-electron pairs of the Pb2+ cations are probably located.